(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article substantiates the need to study rural tourism through the prism of sustainable development of rural areas of Kyrgyzstan. Poverty is an acute problem. The authors believe that sustainable rural tourism can be an important tool for improving the social situation in villages.. The authors have developed recommendations for the development of rural tourism, which will improve the quality of life of rural families in Kyrgyzstan.